Barriers to Hepatitis C Virus Treatment in a Canadian HIV-Hepatitis C Virus Coinfection Tertiary Care Clinic - Meaghan McLaren; Gary Garber; Curtis Cooper (Canadian Journal of Gastroenterology)
BACKGROUND: Despite demonstrated efficacy in HIV-hepatitis C virus (HCV) coinfection, not all patients initiate, complete or achieve success with HCV antiviral therapy.